The correlation between electronic structure and antitumor activity of a seletive focal adhesion kinase inhibitors - Barra de Oliveira, Daniel Augusto (Eclética Química, 2018)
Focal Adhesion Kinase (FAK) is a non-tyrosine kinase responsible to phosphorylate other enzymes associated with signal transduction. This biochemical process plays an important role to control cancer. FAK is found overexpressed in the organism during metastasis. Since FAK may be involved in the invasion and metastasis of cancer, novel molecules based on drug design have been synthesized over the past few years. The inhibitors are designed to mimic the natural substrate which is the ATP molecule. This work studied the hydrogen bonds performed between inhibitors and FAK and other electronic properties involved in this interaction. The molecular structure of FAK docked with the inhibitors was simulated using classical molecular dynamics. FAK/ inhibitor complex obtained by dynamic was optimized using quantum mechanical ab-initio calculation. Our results show that all inhibitors interact with Cys502 located in the FAK-binding site. Ab-initio calculations show that HOMO orbital is situated under Met499 and Glu500 amino acids indicating chemical reactivity in this region. The results of molecular dynamics combined with quantum chemical calculations show that the sulfonamide has a strong hydrogen bond with close distances, while the thiazole has a weak hydrogen bond with long distances. Sulfonamide has known good activity against FAK while the thiazole molecule has an unknown activity. These results allow predicting that the molecule of thiazole is a not good inhibitor to FAK inhibition.